2018
DOI: 10.1371/journal.pone.0193952
|View full text |Cite
|
Sign up to set email alerts
|

Access to primary care for socio-economically disadvantaged older people in rural areas: A qualitative study

Abstract: ObjectiveWe aim to explore the barriers to accessing primary care for socio-economically disadvantaged older people in rural areas.MethodsUsing a community recruitment strategy, fifteen people over 65 years, living in a rural area, and receiving financial support were recruited for semi-structured interviews. Four focus groups were held with rural health professionals. Interviews and focus groups were audio-recorded and transcribed. Thematic analysis was used to identify barriers to primary care access.Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 25 publications
1
47
0
4
Order By: Relevance
“…Participants in our study perceived that older adults are 'set in their ways' or have low self-efficacy, and do not accept supports. Ford and colleagues report that health professionals perceive that the inconsistent use of primary care services by older adults is due the gap between their expectations and the adequacy of service provision [27]. Others argue that preferences, goals, and motivational priorities may change in aging, related to adaptation to losses as well as psychological development wherein new viewpoints and roles develop [28].…”
Section: Discussionmentioning
confidence: 99%
“…Participants in our study perceived that older adults are 'set in their ways' or have low self-efficacy, and do not accept supports. Ford and colleagues report that health professionals perceive that the inconsistent use of primary care services by older adults is due the gap between their expectations and the adequacy of service provision [27]. Others argue that preferences, goals, and motivational priorities may change in aging, related to adaptation to losses as well as psychological development wherein new viewpoints and roles develop [28].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on CWL for attachment to a GP in Quebec found in 8.5% of cases where patients were not attached to the GP to whom they had been assigned, it was because they had missed their appointment [ 32 ]. Several studies have found that, in certain populations, patients with lower levels of social support were more likely to miss appointments [ 72 74 ]. Also, patients from more socially advantaged areas, by having someone such as a spouse to help explain their health status and advocate for their needs to the CWL nurse, may be more likely to be attached to a GP.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because older people can have vague/irregular symptoms in combination with aging, meaning that there are unavoidable symptoms accompanied by prejudices [24,26,27,28]. However, there has been no study on the relationship between HSB and health outcomes, as well as aging [29,30]. Future research should investigate this relationship and interventions for improving older people's HSB should be developed.…”
Section: Discussionmentioning
confidence: 99%